Expert Meeting on Green Islam: Igniting Faith-Led Environmentalism Action in Indonesia - Jannah, Aptiani Nur (Studia Islamika, 2024)
Mainstreaming Green Islam is an important challenge. This Islamic value-based movement needs to spur the government to make more substantive policies and act decisively against those who cause serious environmental damage. To discuss it further, UIN Jakarta’s Center for the Study of Islam and Society (PPIM) through the Religious Environmentalism Actions (REACT) program held an Expert Meeting on June 27, 2024. The Religious Environmentalism Actions (REACT) program is an initiative driven by UIN Jakarta’s Center for the Study of Islam and Society (PPIM) aiming to strengthen the role of young people and religious organizations in promoting a sustainable environment in Indonesia. Through evidence-based knowledge and policy advocacy, this program is expected to make a significant contribution to strengthening the actions of the faith-based environmental movement. In addition, this program also aims to increase public awareness and capacity related to environmental issues and climate change through capacity building and public campaigns.